2016
DOI: 10.1037/ort0000157
|View full text |Cite
|
Sign up to set email alerts
|

A mental health intervention strategy for low-income, trauma-exposed Latina immigrants in primary care: A preliminary study.

Abstract: Latinos in the United States face significant mental health disparities related to access to care, quality of care, and outcomes. Prior research suggests that Latinos prefer to receive care for common mental health problems (e.g., depression and anxiety disorders) in primary care settings, suggesting a need for evidence-based mental health services designed for delivery in these settings. This study sought to develop and preliminarily evaluate a mental health intervention for trauma-exposed Latina immigrants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 73 publications
2
31
0
Order By: Relevance
“…Single interventions described for community-based mental health services pertained to the training of (future) healthcare workers and cultural brokering [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Single interventions described for community-based mental health services pertained to the training of (future) healthcare workers and cultural brokering [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , …”
Section: Resultsmentioning
confidence: 99%
“…In terms of “cultural brokering” [ 12 ], community peers [ 17 , 18 , 19 , 20 , 21 ], bilingual gatekeepers [ 22 ], and ethnic matching of therapists and patients [ 13 , 24 ] were identified. Complex interventions constitute school-based programs to screen (and sometimes, also to treat) children and adolescents from migrant and refugee communities for mental health problems [ 16 , 25 , 26 , 27 , 28 , 29 ], mental health promotion in community day centers [ 30 , 31 ], and by community organizations [ 32 , 33 ] and various other community-based mental health services [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Screening tools for psychosocial risk assessments were also used [ 20 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…The acceptability of the intervention may have been enhanced by the availability of transport and free childcare. Earlier studies showed lack of transport to be a reason for drop outs [26, 49, 50]. Similarly, free crèche service was provided in a room adjacent to the PHP group intervention room, mothers were free to go and check their children as they pleased.…”
Section: Discussionmentioning
confidence: 99%
“…The PCL has good reliability and validity with structured interviews for PTSD (Blanchard et al, 1996), and it has been used in studies of Latino immigrants (Eisenman et al, 2008; Fortuna et al, 2008; Kaltman et al, 2017, under review). Presumptive PTSD was defined by a score ≥ 30 (National Center for PTSD, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…This investigation consisted of a follow-up of patients in a previous/parent study addressing the effectiveness of a collaborative care program (Kaltman, Watson, Campoli, Serrano, Kirkpatrick, Talisman, Mete, and Green, 2017, Evaluation of behavioral health services in primary care clinics serving low-income Latino immigrants, under review). The parent study was implemented in two clinics that are part of a network of primary care clinics providing care to low-income uninsured county residents in Maryland.…”
Section: Study Backgroundmentioning
confidence: 99%